Tropomyosin position on F-Actin revealed by EM reconstruction and computational chemistry - Li, Xiaochuan (Edward); Tobacman, Larry S.; Mun, Ji Young; Craig, Roger; Fischer, Stefan; Lehman, William (Biophysical journal, 2011)
Electron microscopy and fiber diffraction studies of reconstituted F-actin-tropomyosin filaments reveal the azimuthal position of end-to-end linked tropomyosin molecules on the surface of actin. However, the longitudinal z-position of tropomyosin along F-actin is still uncertain. Without this information, atomic models of F-actin-tropomyosin filaments, free of constraints imposed by troponin or other actin-binding proteins, cannot be formulated, and thus optimal interfacial contacts between actin and tropomyosin remain unknown. Here, a computational search assessing electrostatic interactions for multiple azimuthal locations, z-positions, and pseudo-rotations of tropomyosin on F-actin was performed. The information gleaned was used to localize tropomyosin on F-actin, yielding an atomic model characterized by protein-protein contacts that primarily involve clusters of basic amino acids on actin subdomains 1 and 3 juxtaposed against acidic residues on the successive quasi-repeating units of tropomyosin. A virtually identical model generated by docking F-actin and tropomyosin atomic structures into electron microscopy reconstructions of F-actin-tropomyosin validated the above solution. Here, the z-position of tropomyosin alongside F-actin was defined by matching the seven broad and narrow motifs that typify tropomyosin's twisting superhelical coiled-coil to the wide and tapering tropomyosin densities seen in surface views of F-actin-tropomyosin reconstructions. The functional implications of the F-actin-tropomyosin models determined in this work are discussed.
Gesehen am 25.08.2022